A high spatial resolution soil carbon and nitrogen dataset for the northern permafrost region based on circumpolar land cover upscaling - Juri Palmtag (Department of Human Geography, Stockholm University); Jaroslav Obu (Department of Geosciences, University of Oslo); Peter Kuhry (Department of Physical Geography, Stockholm University); Andreas Richter (Centre for Microbiology and Environmental Systems Science, University of Vienna); Matthias B. Siewert (Department of Ecology and Environmental Science, Umeå University); Niels Weiss (Northwest Territories Geological Survey, Government of the Northwest Territories); Sebastian Westermann (Department of Geosciences, University of Oslo); Gustaf Hugelius (Department of Physical Geography, Stockholm University) (Earth System Science Data, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:1679374 The abstract is available here: https://uscholar.univie.ac.at/o:1679374